CD45RA, CD8β, and IFNγ Are Potential Immune Biomarkers of Human Cognitive Function - Esgalhado, André J.; Reste-Ferreira, Débora; Albino, Stephanie E.; Sousa, Adriana; Amaral, Ana Paula; Martinho, António; Oliveira, Isabel T.; Verde, Ignacio; Lourenço, Olga; Fonseca, Ana M.; Cardoso, Elsa M.; Arosa, Fernando A. (Frontiers in Immunology, 2020)
There is increasing evidence that in humans the adaptive immunological system can influence cognitive functions of the brain. We have undertaken a comprehensive immunological analysis of lymphocyte and monocyte populations as well as of HLA molecules expression in a cohort of elderly volunteers (age range, 64-101) differing in their cognitive status. Hereby, we report on the identification of a novel signature in cognitively impaired elderly characterized by (1) elevated percentages of CD8+ T effector-memory cells expressing high levels of the CD45RA phosphate receptor (Temrahi); (2) high percentages of CD8+ T cells expressing high levels of the CD8β chain (CD8βhi); (3) augmented production of IFNɣ by activated CD4+ T cells. Noteworthy, CD3+CD8+ Temrahi and CD3+CD8βhi cells were associated with impaired cognition. Cytomegalovirus seroprevalence showed that all volunteers studied but one were CMV positive. Finally, we show that these phenotypic and functional features are concomitant to an increased frequency of the HLA-B8 serotype, that belongs to the ancestral haplotype HLA-A1, B8, Cw7, DR3, DQ2, among cognitively impaired volunteers. To our knowledge, this is the first proof in humans linking the amount of cell surface CD45RA and CD8β chain expressed by CD8+ Temra cells, and the amount of IFNɣ produced by activated CD4+ T cells, with impaired cognitive function in the elderly.